Autoeficácia, qualidade de vida e suporte social relacionados ao esporte de rendimento - Aizava, Paulo Vitor Suto (2011)
This study had as objective to investigate the degree of associations between general perceived self efficacy, quality of life level (QL) and social support in performance volleyball athletes. The subjects were 86 adult male performance volleyball athletes, of municipal level (n=47; 54,7%), state level (n=26; 30,2%) and national level (n=13; 15,1%), who participated in competitions in the 2010 season. As instruments, it was used: the athlete identification sheet, Scale of General Perceived Self Efficacy (SGPSE), Medical Outcomes Study 36 - item short - Form Survey (SF-36) and the Medical Outcomes Study Social Support Survey (MOS-SSS). The data was collected individually in athlete's competitions and training locals. For data analysis, it was used: Kolmogorov-Smirnov test (P≤0.05), Cronbach's alpha coefficient, Levene's test, One-way ANOVA with Scheffe's post hoc , Kruskal-Wallis test, Mann-Whitney's U test, ANOVA - repeated measures with Bonferroni's post hoc, test of sphericity Mauchly's W test and the Greenhouse-Geiser test. For the associations, it was used the Association Chi-square Test, Fisher exacts test, Cramer's V, Spearman's correlation and Poisson regression with robust adjustment. The results showed: all athletes demonstrated a high level of general self-efficacy, perceived good level of social support and quality of life. Comparison between scales of social support for athletes at the municipal and state level, highlighted the positive social interaction (P≤0,01), while for the quality of life the scale that stood out was the functional capacity (P≤0.05) at all levels of competitions; the comparison of QL considering athletes' ages, there was significant difference in the physical aspects limitation scale for athletes 23 - 30 years old when compared to athletes 31 - 38 years old (P=0,01) and pain for athletes who ranged from 15 - 22 years old when compared to athletes 23 - 30 years old (P=0,03); the self-efficacy was associated with age (P=0,04), practice time (P=0,05), with the scales of social support: material support (P=0,05), emotional (P=0,00) and positive social interaction (P=0,05), and QL scales: vitality (P=0,05), social aspects (P=0,03) and emotional aspects limitation (P=0,01); for the athletes of the Brazilian national team, there was a significant correlation between the self-efficacy scale and material support (r=0,78) of social support. Therefore, one concludes: general self-efficacy had association with good QL and high levels of social support in the context of volleyball athletes. In this sense, sport for these athletes has created favorable conditions for personal and athletic performance.